THE HYBRID ROLE OF FOUNDER-EDITORS IN REGIONAL DIGITAL MEDIA: A CASE FROM GORAKHPUR, INDIA - Dubey, Harsh Vardhan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rise of hyperlocal digital news sites in India is symptomatic of a broader shift in the media landscape, in which digital technologies allow for the empowerment of minor actors against mainstream hegemony. Such platforms tend to be established and run by local journalists interested in offering community-based coverage in the wake of a lack of proper coverage by mainstream media (Ali, 2019; Kumar, 2021). In places such as Gorakhpur, hyperlocal shops have not only become sources of information but also sites of civic conversation, responsibility, and localized narrative.